Ljubljanska župana Josef Suppan (1869-1871) in Karel Deschmann (1871-1873) - Matić, Dragan (Studia Historica Slovenica, 2017)
The German Mayors of Ljubljana, Josef Suppan and Karel Deschmann, were among the top politicians of Carniolan Germans, and they worked closely all the time - Suppan's deputy Mayor and mayoral successor was Deschmann. Their terms as mayors (1869-1871 and 1871-1874) signified a period of German dominance in Carniola and Ljubljana. Despite the disagreements with the Slovenian majority in the provincial assembly and the intensification of international tensions, it is not possible to deny the positive effects of the German municipal authority on the economic, social, and cultural development of Ljubljana.
Keywords: Dežman, Dragotin; kulturna zgodovina; Ljubljana; politična zgodovina; Slovenija; Zupan, Jožef; župani